IL-23 promotes T-cell mediated cardiac inflammation but protects the heart from fibrosis. (25th November 2020) - Vdovenko, D; Wijnen, W.J; Zarak Crnkovic, M; Blyszczuk, P; Bachmann, M; Costantino, S; Paneni, F; Camici, G.G; Luescher, T.F; Eriksson, U
Abstract: Introduction: Cardiac inflammation varies widely and, in some cases, triggers autoimmune myocarditis and further inflammatory dilated cardiomyopathy (iDCM) and heart failure. In children, myocarditis leads to cardiomyopathy in almost half of affected individuals and up to 20% of sudden death cases in young adults have been reported to be due to myocarditis. IL-12 and IL-23 belong to the same family of cytokines known to mediate inflammatory conditions. Both regulate the differentiation of T cells: IL-12 promotes towards IFN-gamma-producing Th-1 cells, while IL-23 induces IL-17-producing Th-17 cells. Heart-reactive CD4+Th17 cells play a leading role in the development of myocarditis, however, literature reports excessiveness of IL-23 in Th17-derived IL-17 production. Therapeutic strategies blocking IL-23 were suggested as a promising approach, though the specific role of IL-23 in pathogenesis is unclear and the long-term perspectives stay elusive. Purpose: We aim to explore the role IL-23 compared to IL-12 in the manifestation of cardiac autoimmune myocarditis. Methodology: We use dendritic cell (DC) model of experimental autoimmune myocarditis in IL-12 and IL-23-deficient mice. Mice were injected with bone marrow-derived in vitro activated and loaded with cardiac-specific peptide DCs. This model mimics natural processes taking place during heart inflammation and provides a unique method to address the role of DCs-derived cytokines. Cardiac inflammation, as well as remodeling and heart function, were analysed at the acute and chronic stages of the disease. Results: Surprisingly, all mice developed acute myocarditis, though wt receiving IL-23−/−bmDCs showed a twofold decrease in heart-infiltrating T cells and lower numbers of Th17 population. Further decrease of heart-infiltrating T cells appeared upon total systemic IL-23 deficiency. In comparison to IL-12, directly inducing differentiation of IFN-gamma–producing Th1, IL-23 cannot induce Th17 differentiation. None of the two cytokines affect proliferation, though, IL-23 activates T cell migratory potential and increases T cell migration by twofold. At the same time, deficiency of IL-23-production by bmDCs leads to lower migration of T cells. We also show an involvement of RhoA, and the other Rho GTPases, in the mechanism of migration as blocking revoke the IL-23 effect on T cells. Moreover, we further observed more fibrosis and worse heart functioning in IL-23−/−, but not IL-12−/− mice at the chronic stage what underlines the importance of IL-23-dependent T cell trafficking in the resolution of the acute stage of autoimmune myocarditis. Conclusion: Our observations underline IL-23 as an important cytokine responsible for T cell trafficking and resolution of the inflammation in autoimmune myocarditis. Therapeutic approaches involving inflammatory cytokine targeting are a promising clinical perspective though IL-23 deficiency might lead to increased cardiac remodeling and iDCM progression. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The Swiss National Science Foundation